The Influence of Service Quality and Hotel Image on the Satisfaction and Loyalty of Tourists Staying at Artotel Group Hotel Bali - Pangkerego, Paulus Davidson; Sudiarta, I Nyoman; Antara, Made (International Journal Labs, 2023)
In this comprehensive study, the focus revolves around delineating the intricate dynamics between service quality, hotel image, tourist satisfaction, and loyalty within the context of Artotel Group Hotel Bali. The pivotal role of service quality emerges as a central theme, elucidating that the realization of good service quality hinges upon the proficiency of human resources. The study underscores the significance of competent personnel in achieving maximum service values, which is further augmented by the presence of well-equipped infrastructure and facilities. Drawing on the theoretical framework of satisfaction, the researchers employ a quantitative descriptive method to delve into the nuances of these interconnections. Unveiling the outcomes of their investigation, the study propounds that both service quality and the hotel image wield a positive and statistically significant impact on tourist satisfaction during their sojourn at Artotel Group Hotel Bali. This illuminates a direct correlation wherein heightened service quality and a positive hotel image contribute to an elevated level of satisfaction among tourists residing at Artotel Group Hotel Bali. Consequently, the study not only underscores the critical importance of service quality and hotel image but also establishes a concrete link between these factors and the overall satisfaction of tourists, providing valuable insights for enhancing the hospitality experience at Artotel Group Hotel Bali.